Enhancing the Mechanical and Barrier Properties of Seaweed-Cassava Starch Bioplastics with Natural Additives for Sustainable Food Packaging - Etin Diah Permanasari; Larisa Mandalini (CV. Get Press Indonesia, 2026)
The growing accumulation of petroleum-based plastic waste has intensified the search for biodegradable alternatives from renewable resources. This study investigated the effect of clove essential oil (CEO) on the mechanical and barrier properties of composite bioplastic films from semi-refined carrageenan and cassava starch (30:70) with 30% glycerol. Unlike previous studies using purified biopolymers or focusing solely on antimicrobial effects, this work uniquely evaluates CEO as a dual-function agent plasticizer and hydrophobic barrier enhancer within a low-cost carrageenan–starch matrix to identify the optimal loading for balanced packaging performance. Films were prepared by solution-casting with CEO at 0, 0.5, 1.0, 1.5, and 2.0% (w/w). Increasing CEO content decreased tensile strength (18.2 to 12.1 MPa) and Young's modulus (612 to 365 MPa), while elongation increased (22.4% to 41.6%). WVP and oxygen permeability decreased by 39% and 43%, respectively, alongside an increase in contact angle (68.4° to 89.6°), indicating enhanced hydrophobicity. FTIR confirmed physical dispersion without new covalent bonding. Films remained biodegradable, though higher CEO slowed degradation. The 1.0–1.5% CEO formulation offered the most balanced combination of flexibility, barrier performance, and degradability for sustainable food packaging.